History of surgical approaches in orthopaedics - Bartoníček, Jan; Naňka, Ondřej (International orthopaedics, 2025)
Surgical approaches in bone surgery have undergone a long evolution over more than 130 years. While a number of publications have been devoted to the history of internal fixation, surgical approaches have remained neglected from this perspective. The development of approaches in musculoskeletal surgery is inextricably linked to four personalities. Theodor Kocher, in 1892, pointed out that descriptions of surgical approaches must be an essential part of surgical textbooks of operative techniques; James Edwin Thompson, in 1918, formulated the basic requirements for the surgical approaches to the skeleton of limbs; Arnold Kirkpatrick Henry published the first textbook of surgical approaches in 1927 and presented the concept of internervous planes in 1945; in the same year, Toufick Nicola created the first comprehensive atlas of surgical approaches to bones and joints of limbs, the pelvis and spine.
Keywords: ortopedie; Orthopedic Procedures; History of internal fixation; Orthopedics; dějiny 20. století; dějiny 19. století; ortopedické výkony; Humans; History, 20th Century; History of orthopaedics; lidé; dějiny 21. století; Surgical approaches; History, 21st Century; History, 19th Century